Case report: A germline CHEK1 c.613 + 2T>C leads to a splicing error in a family with multiple cancer patients - Qian, Jun; Peng, Min; Li, Yanan; Liu, Wei; Zou, Xinwei; Chen, Huafei; Zhou, Sujuan; Xiao, Sheng; Zhou, Jinhua (Frontiers in Oncology, 2024)
Background: Genome instability plays a crucial role in promoting tumor development. Germline mutations in genes responsible for DNA repair are often associated with familial cancer syndromes.A noticeable exception is the CHEK1 gene. Despite its well-established role in homologous recombination, germline mutations in CHEK1 are rarely reported.In this report, we present a patient diagnosed with ovarian clear cell carcinoma who has a family history of cancer. Her relatives include a grandfather with esophageal cancer, a father with gastric cancer, and an uncle with a brain tumor. The patient carried a typical genomic profile of clear cell carcinoma including mutations in KRAS, PPP2R1A, and PIK3R1. Importantly, her paired peripheral blood cells harbored a germline CHEK1 mutation, CHEK1 exon 6 c.613+2T>C, which was also found in her father. Unfortunately, the CHEK1 status of her grandfather and uncle remains unknown due to the unavailability of their specimens. Further evaluation via RT-PCR confirmed a splicing error in the CHEK1 gene, resulting in truncation at the kinase domain region, indicative of a loss-of-function mutation.This case highlights a rare germline CHEK1 mutation within a family with a history of cancer. The confirmed splicing error at the mRNA level underscores the functional consequences of this mutation. Documenting such cases is vital for future evaluation of inheritance patterns, clinical penetrance of the mutation, and its association with specific cancer types.